Approaches to sustainability in the fishing sector: The case of Cornelis Vrolijk's pelagic fisheries from the Northeast Atlantic - Ortega Ramirez, Mariana (author) (2017)
The meaning of what a sustainable fish food product demands can differ among the stakeholders who are knowledgeable in the product system. This thesis applies methods and tools from the field of industrial ecology to understand what sustainability means when it comes to a pelagic fish product from the Northeast Atlantic. The study covers a need of the company Cornelis Vrolijk to evaluate their environmental performance. An LCA study is performed on four of their products: blue whiting, herring, mackerel and horse mackerel. Besides hotspot identification, the practicality of the suggested improvements proposed is analysed by looking at the case of fuel sustainable procurement. Lastly, sustainability indicators for the company´s CSR are proposed. The LCA study is conducted in team, with other industrial ecology master student. The study took place from February to August 2017. Thesis research in the context of MIND, an Erasmus Mundus Industrial Ecology master program. Involved universities: Leiden University and TU Delft in the Netherlands, and Graz University in Austria. Industrial Ecology